Expert consensus on the use of systemic glucocorticoids for managing eosinophil-related diseases - del Pozo, Victoria; Bobolea, Irina; Rial, Manuel J.; Espigol-Frigolé, Georgina; Solans Laqué, Roser; Hernández-Rivas, Jesús María; Mora, Elvira; Crespo-Lessmann, Astrid; Izquierdo Alonso, José Luis; Domínguez Sosa, María Sandra; Maza-Solano, Juan; Atienza-Mateo, Belén; et al. (Frontiers in Immunology, 2024)
Eosinophil-related diseases represent a group of pathologic conditions with highly heterogeneous clinical presentation and symptoms ranging from mild to critical. Both systemic and localized forms of disease are typically treated with glucocorticoids. The approval of novel biologic therapies targeting the interleukin-5 pathway can help reduce the use of systemic glucocorticoids (SGC) in eosinophilic diseases and reduce the risk of SGC-related adverse effects (AEs). In this article, a panel of experts from different medical specialties reviewed current evidence on the use of SGC in two systemic eosinophilic diseases: Eosinophilic Granulomatosis with PolyAngiitis (EGPA) and HyperEosinophilic Syndrome (HES); and in two single-organ (respiratory) eosinophilic diseases: Chronic RhinoSinusitis with Nasal Polyps (CRSwNP) and Severe Asthma with Eosinophil Phenotype (SA-EP), and contrasted it with their experience in clinical practice. Using nominal group technique, they reached consensus on key aspects related to the dose and tapering of SGC as well as on the initiation of biologics as SGC-sparing agents. Early treatment with biologics could help prevent AEs associated with medium and long-term use of SGC.